Asthma medication prescribing before, during and after pregnancy: a study in seven European regions. Issue 1 (19th January 2016) - Charlton, Rachel A; Pierini, Anna; Klungsøyr, Kari; Neville, Amanda J; Jordan, Susan; de Jong-van den Berg, Lolkje T W; Thayer, Daniel; Bos, H Jens; Puccini, Aurora; Hansen, Anne V; Gini, Rosa; Engeland, Anders; et al.
Abstract : Objectives: To explore utilisation patterns of asthma medication before, during and after pregnancy as recorded in seven European population-based databases. Design: A descriptive drug utilisation study. Setting: 7 electronic healthcare databases in Denmark, Norway, the Netherlands, Italy (Emilia Romagna and Tuscany), Wales, and the Clinical Practice Research Datalink representing the rest of the UK. Participants: All women with a pregnancy ending in a delivery that started and ended between 2004 and 2010, who had been present in the database for the year before, throughout and the year following pregnancy. Main outcome measures: The percentage of deliveries where the woman received an asthma medicine prescription, based on prescriptions issued (UK) or dispensed (non-UK), during the year before, throughout or during the year following pregnancy. Asthma medicine prescribing patterns were described for 3-month time periods and the choice of asthma medicine and changes in prescribing over the study period were evaluated in each database. Results: In total, 1 165 435 deliveries were identified. The prevalence of asthma medication prescribing during pregnancy was highest in the UK and Wales databases (9.4% (CI95 9.3% to 9.6%) and 9.4% (CI95 9.1% to 9.6%), respectively) and lowest in the Norwegian database (3.7% (CI95 3.7% to 3.8%)). In the year before pregnancy, the prevalence of asthma medication prescribing remained constant in all regions. Prescribing levels peaked during the second trimester of pregnancy and were at their lowest during the 3-month period following delivery. A decline was observed, in all regions except the UK, in the prescribing of long-acting β-2-agonists during pregnancy. During the 7-year study period, there were only small changes in prescribing patterns. Conclusions: Differences were found in the prevalence of prescribing of asthma medications during and surrounding pregnancy in Europe. Inhaled β-2 agonists and inhaled corticosteroids were, however, the most popular therapeutic regimens in all databases.